Benchmarking risk management within the international water utility sector. Part II: A survey of eight water utilities. - MacGillivray, Brian H.; Sharp, J. V.; Strutt, J. E.; Hamilton, Paul D.; Pollard, Simon J. T. (Taylor & Francis, 2007)
Risk management in the water utility sector is fast becoming explicit. Here, we describe application of a capability model to benchmark the risk management maturity of eight water utilities from the UK, Australia and the USA. Our analysis codifies risk management practice and offers practical guidance as to how utilities may more effectively employ their portfolio of risk analysis techniques for optimal, credible, and defensible decision making. For risk analysis, observed good practices include the use of initiation criteria for applying risk assessment techniques; the adoption of formalised procedures to guide their application; and auditing and peer reviews to ensure procedural compliance and provide quality assurance. Additionally, we have identified common weaknesses likely to be representative of the sector as a whole, in particular a need for improved risk knowledge management and education and training in the discipline.
Keywords: Maturity model; risk analysis; risk management; water sector